Connectedness and The Impact of Major Spillovers on Global Stock Markets: An Empirical Analysis - Khalid, Syed Mohd; Dhiman, Babli; Birau, Ramona; Popescu, Virgil; Margaritescu, Stefan (International Journal of Accounting and Economics Studies, 2025)
The diversity of the global stock market composition depicts distinct degrees of cross-market contagion. Market contagion plays a prominent role in the transmission mechanism. Significant increases in Spillovers were observed after the October 1989 stock market fall. The economists developed an interest in analysing the spillovers after the middle of the 1990s with the extension of financial crises amidst the advanced and emerging economies. Highly advanced and developed nations were also influenced, whose procedures and strategies were applauded by market specialists and financial institutions. DCC-GARCH and BEKK-GARCH were used to evaluate the spillover effect between the global stock markets. This study examines the major spillover impacts on the global stock markets. In this study, the [Joint]dccα1 showed that in the short-run spillover between variables, all the variables had significant p-values, which indicate the short-run spillover except SSE, ASX-200, and TSX, where p-values are insignificant. The [Joint] dccβ1 shows the long-run spillover between variables; all the variables show the long-run spillover as their p-values are significant. They also show a strong positive correlation between variables, as the coefficients are near 1. BEKK-GARCH authorised the results, showing strong positive conditional correlation between the global stock exchanges.